ETHNOMATHEMATICS: OPERASI BILANGAN BULAT PADA ATURAN “PETEMUAN” MASYARAKAT BALI - Jero Budi Darmayasa; Wahyudin Wahyudin; Tatang Mulyana (Mathematics Education And Application Journal (META), 2019)
This qualitative research with case study model aims to explore ethnomathematics contained in the pre-marital culture of Balinese, especially the Bali Mula people. Based on the results of interviews, Focus Group Discussion (FGD), participant observation, and documentation analysis, it was found that there were several basic calculations in determining the merits of a mate in the Petemuan. After being examined and analyzed, the Ethnomathematics of the Petemuan was matched with the Number Operations in Junior High School Mathematics subjects.